Review: Sex Chromosome Evolution and the Expression of Sex-Specific Genes in the Placenta - Graves, J.A.M. (Placenta (Eastbourne), 2010)
Sex chromosomes have a disproportionate influence on health and disease. Both the X and Y are atypical in gene content and activity, as a result of their unique evolutionary trajectory. The X and Y chromosomes originated in a pair of autosomes, and differentiated as the Y chromosome degenerated progressively. The Y contains few active genes and is composed largely of repetitive DNA sequences. Most Y genes have copies on the X from which they evolved; this includes even the sex-determining gene SRY as well as several genes required for spermatogenesis. The X contains a disproportionate number of genes that affect reproduction and brain function (or both). It is also subject to inactivation in females, so that females are mosaics composed of patches of tissue that express only the genes on either the maternally or the paternally derived X chromosome. Several widely expressed genes on the Y chromosome code for male-specific proteins that provoke an immune reaction in females; this HY antigen has a measurable effect on maternal-fetal incompatibility. Imprinted paternal X inactivation in rodent extraembryonic tissues would be expected to mitigate the effect of foreign paternal antigens; however, paternal inactivation seems not to occur in the human placenta.